Effect of confinement on the static and dynamic indentation response of model ceramic and cermet materials. (December 2017) - Pickering, E.G.; O'Masta, M.R.; Wadley, H.N.G.; Deshpande, V.S.
Highlights: Model ceramics and cermets suitable for laboratory investigations identified. Effect of confinement on the dynamic response of model cermets and ceramics quantified. The cracking modes of model ceramics and cermets identified under quasi-static and dynamic loading. Abstract: The effect of confinement on the localized impact response of ceramic and cermet tiles is investigated. A scoping study was first conducted using alumina and TiC/Ni cermet tiles encased in a metal matrix composite (MMC) and impacted by high velocity steel balls. The investigation revealed that increasing the MMC casing thickness reduced the cracking in the ceramic (alumina) tile but had a much smaller effect on the cermet tile. This motivated a detailed experimental investigation of the effect of lateral confining pressure on the static and dynamic indentation response of granite and Corian® tiles that serve as model ceramic and cermet materials, respectively. Quasi-static indentation resulted in comminution under the indenter and the formation of radial cracks in the granite tiles, with the number of radial cracks decreasing with increasing confining pressure. By contrast, the plastic indentation and small shallow radial cracks observed in the Corian® tiles were unaffected by variations in the confining pressure. The loading imposed by the high velocity impact of a steel ball resulted in conical and lateral cracks as well as radial cracks and comminution in the granite tiles. Intriguingly, while the cone and radial cracks were suppressed by confining pressure, the lateral cracks appeared only at the higher confining pressures. By contrast, the strain rate sensitivity of the yield strength of the Corian® reduced the plastic indentation under dynamic loading, but this in turn promoted the formation of radial cracks which decreased in number with increasing confining pressure. No lateral cracks, conical cracks or comminution was observed in the Corian® . The study shows that confining pressure has a less significant effect on cermets compared to ceramics. Since confinement systems add considerable weight to ceramic-based ballistic protection systems, this study suggests that the use of lightly confined cermets could reduce the overall weight of ballistic protection systems.